(untitled) (Polish Yearbook of International Law, 2023)
The international community has repeatedly committed to the implemen- tation of the Women, Peace and Security Agenda (WPS) initiated by UN Security Council Resolution 1325. Yet progress on the ground has been slow and sporadic, which can also be seen in the Ukrainian peace process starting from 2014. This article looks at the different areas of inclusion of women in both policy and practice, in order to highlight the existing discrepancies and draw attention to the need to improve the international community’s approach to inclusion. The role of the different international actors (e.g. UN, EU, NATO, OSCE) is assessed in terms of their contribution to or emphasis on the need for inclusion. The article also aims to illustrate how international law and policy can be utilised by civil society activists in order to implement inclusion in practice, thereby highlighting the potential for international legal norms to positively impact enhancement of the position of women in (post)conflict situations around the world.